POLITICS AND TOURISM DEVELOPMENT: THE CASE OF NORTHERN PROVINCE - SRI LANKA - Sivesan, S. (University of Jaffna, 2017)
The concept of tourism development has become the focus of increasing attention among tourism practitioners and scholars alike. Little research, however, has been undertaken to investigate the relationship between politics and tourism development in Sri Lanka from the perspective of stakeholders. The main objective of this study is to explore the relationship between politics and tourism development in Northern Province – Sri Lanka. Drawing on study in Northern Province in Sri Lanka, it reveals the ways in which political instability and political interferences have viewed as major obstacles to tourism development. Further, this study concludes that stakeholders, including the state, the provincial authorities and investors, have a willingness to promote the industry. This study offers meaningful information for developing strategy on the part of tourism management in the absence of political interferences.
Keywords: Tourism development; Sri Lanka; Political instability; Liberal ize; Economic policy